Integrating Practical Skills Into Multimodal Transportation Education In Indonesia - Markus Yando; Larsen Barasa; Marudut Bernadtua Simanjuntak (International Journal of Educational Development, 2024)
This research explores the integration of practical skills into multimodal transportation education in Indonesia. Through qualitative analysis of 50 Indonesian cadets, the study examines the balance between theoretical knowledge and practical application, the effectiveness of current educational practices, and recommendations for improvement. The findings reveal a strong consensus among cadets on the importance of practical skills alongside theoretical knowledge. While some practical training is provided, there is a need for more hands-on experiences and industry exposure. Recommendations include revising curricula to include more practical exercises and case studies, strengthening industry partnerships, enhancing instructor skills, integrating soft skills development, and promoting lifelong learning. These recommendations aim to better prepare students for the demands of the transportation industry and enhance their employability. By implementing these recommendations, educational institutions can bridge the gap between theory and practice, ultimately improving the quality and relevance of transportation education in Indonesia.